Pengaruh Corporate Governance Terhadap Financial Statement Fraud - Nuraisyah, Ratna Putri; Setiawati, Erma (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to obtain empirical evidence and to analyze the effect of corporate governance’s mechanism such as internal control, managerial ownership, institutional ownership, liquidity ratios, and profitability ratios of financial statment fraud. This study uses secondary data from the company’s annual report for 2013-2021. The sample in this study is a company listed on the Jakarta Islamic Index 30 (JII 30) whoch has consistently entered for the las ten years. According to the certain criteria as many 45 sample for the last nine years. The analysis used in this study is logistic regression analysis. The research results show that internal control, managerial ownership, institutional ownership, profitability ratios influence financial statement fraud. Meanwhile, the liquidity ratio has no effect on financial statement fraud.Kata Kunci: Financial statement fraud, good corporate governance, internal control, managerial ownership, institutional ownership, liquidity ratios, profitability ratios